Nursing Education Institutes’ Administrators’ Competences in the 21th Century - Napasanan Piyasiripan (Health Notions, 2020)
This documentary research aimed to study and to present approaches for developing competencies of administrators in nursing education institutes in the 21th century. The samples were documents related to both domestic and international documents related to approaches for developing capacities of administrators in nursing education institutes in the 21th century. The result showed that the approaches for developing capacities of administrators in nursing education institutes in the 21th century consisted of self-development, on the job training, and off the job training that were based on contemplative education for self discovery toward work development within the organization, adult learning with self-study process by self-analysis and behavior adjustment by knowledge exchange, reflective methods, information searching via electronic databases, study tour of a role model for intellectual generation, knowledge from inward to leadership skills practice to become a leader with perfect health. Keywords: nursing education institution; administrators; the 21th century